Genomic diversity of phages infecting probiotic strains of Lactobacillus paracasei - Mercanti, Diego Javier (2015)
Strains of the Lactobacillus casei group have been extensively studied because some are used as probiotics in foods. Conversely, their phages have received much less attention. We analyzed the complete genome sequences of five L. paracasei temperate phages: CL1, CL2, iLp84, iLp1308, and iA2. Only phage iA2 could not replicate in an indicator strain. The genome lengths ranged from 34,155 bp (iA2) to 39,474 bp (CL1). Phages iA2 and iLp1308 (34,176 bp) possess the smallest genomes reported, thus far, for phages of the L. casei group. The GC contents of the five phage genomes ranged from 44.8 to 45.6%. As observed with many other phages, their genomes were organized as follows: Genes coding for DNA packaging, morphogenesis, lysis, lysogeny, and replication. Phages CL1, CL2, and iLp1308 are highly related to each other. Phage iLp84 was also related to these three phages, but the similarities were limited to gene products involved in DNA packaging and structural proteins. Genomic fragments of phages CL1, CL2, iLp1308, and iLp84 were found in several genomes of L. casei strains. Prophage iA2 is unrelated to these four phages, but almost all of its genome was found in at least four L. casei strains. Overall, these phages are distinct from previously characterized Lactobacillus phages. Our results highlight the diversity of L. casei phages and indicate frequent DNA exchanges between phages and their hosts.